Zooplankton community and tributary effects in free-flowing section downstream a large tropical reservoir - Portinho, Jorge L. [UNESP]; Perbiche-Neves, Gilmar; Nogueira, Marcos G. [UNESP] (Wiley, 2016)
This study aimed to evaluate the zooplankton structures and environmental conditions in the interface reservoir-downstream river and tributaries. Zooplankton structure and environmental variables were analyzed in the lacustrine zone of Itaipu Reservoir and downstream this dam at Paraná River and in two lateral tributaries. A total of nine sites were sampled in July 2009 and January 2010 (winter/dry vs. summer/wet). In the free-flowing section downstream of the Itaipu Reservoir (Paraná River), the physical-chemical influence of the dammed water can persist for approximately 15km in the dry period and 30km in the rainy period. The lateral tributaries (Iguaçu and Monday Rivers) introduce sediments (particulate organic and inorganic matter), nutrients and potamoplankton biota that contribute to fluvial restoration, particularly in the dry period when the main river flow is low. The zooplankton community structure and composition varied over space (longitudinal) and time. Rotifers dominated in the lateral tributaries, whereas microcrustaceans from the reservoir were abundant in the Paraná River. The density of zooplankton downstream of the reservoir decreased, with the highest reduction occurring in the first 5km downstream of the dam, however, the species composition persisted in the all free-flowing section downstream studied. Associations were found among zooplankton abundance and environmental variables, mainly the current velocity and water discharge, zooplankton groups had different responses to these variables. Differences in the zooplankton ecological structure along a stretch of the Paraná River clearly indicate the effects of damming and tributaries.
Keywords: Itaipu Reservoir; Lateral inputs; Limnological variables; Zooplankton drift